'QUALITY' CRITICISM Music Reviewing in Australian Rock Magazines. (5th October 2015) - EVANS, MARK
Abstract : Evans' article has a contemporary focus, addressing the nature of reviewing practice in the Australia's two principal 'quality' rock monthlies Juice and Rolling Stone. His study is premised on statistical analyses of the thematic content and address of reviews and provides a valuable framework for understanding two prime loci of reviewing practices which have helped shape a national field of taste. In conducting the statistical analyses presented in this article, the survey periods adopted for data collection were: six years of Rolling Stone, beginning January 1989 and concluding January 1995; and two years of Juice, from the magazine's inception in March 1993 through to March 1995. A database was established from the information contained within the album review sections of each magazine. The chosen fields under which the data was gathered were: the date of publication; the reviewed album's name; the artist's name; the reviewer; the star rating given to the album by the reviewer; and the artist's country of origin.3